Efektivitas ekstrak biji nimba untuk pengendalian ulat kobis (Plutella xylostella) - Rukmowati Brotodjojo (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2014)
Synthetic insecticides have detrimental effect to environment. Botanical insecticides are considered to be safer to the environment. Need seeds contain compounds with insecticidal properties. The aim of this study was to examine the effectiveness of neem seeds extract to control Diamondback moth (DBM). A series of neem seeds extract concentration (0.04 %, 0.08 %, 0.16 %, 0.32 %) and control (without neem extract) were tested on second instar larvae in oral test and contact test. The results showed that neem seeds extract have significant effect on the mortality of second instar DBM larvae 24-72 h after treatment in oral test and 72 h after treatment in contact test. In the oral test, the neem seeds extract significantly reduced feeding intensity of the larvae 42 h and 72 h after treatment. Subsequently, the extract also significantly reduced the moth emergence. The neem seeds with concentration 0.16 % effectively control DBM second instar larvae 72 h after treatment.Key Words: neem seeds extract, diamondback moth, effectiveness